A framework of mobile banking adoption in India - Ashish Kumar; Sanjay Dhingra; Vikas Batra; Harish Purohit (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Mobile banking is now an important and evolving medium for executing banking transactions. It has a huge potential in a developing country such as India. Our study explores the important antecedents of the mobile banking adoption intention of Indian customers and proposes a comprehensive framework by extending the traditional technology acceptance model (TAM). Along with the two constructs provided by TAM, four customer-oriented constructs have also been measured for this purpose. The conceptual model has been verified empirically, with the data mobilized with the help of a survey from 203 future mobile banking service users. The structural equation modeling (SEM) technique has been undertaken to establish the effect of the antecedents on mobile banking adoption intention. The results demonstrate that, together with the constructs of TAM, viz. perceived usefulness and perceived ease of use, as well as all other relevant behavioral factors, namely subjective norms, personal innovativeness, trust, and self-efficacy have exerted a statistically significant positive effect on the mobile banking adoption intention of customers. The study provides an empirical foundation, which can be useful to banking and mobile services by helping companies to formulate their marketing strategies.
Keywords: 650; adoption intention; mobile banking; perceived ease of use; perceived usefulness; TAM